2015
DOI: 10.1021/jp511615r
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Studies on Structure, Ligand Exchange, and Optical Properties of Ligand-Protected Gold Nanoclusters: Thiolate versus Selenolate

Abstract: Atomically precise thiolate-protected Au nanoclusters (NCs), i.e. Au m (SR) n , have attracted intensive research interest during the past few years. Recently, the synthesis and isolation of selenolate-protected gold clusters (Au m (SeR) n ) via the ligand exchange of thiolate with selenol were achieved, which demonstrated identical compositions to those of thiolate-protected Au NCs. In this study, we perform a comprehensive theoretical study on the structure, electronic structure, and electronic optical absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Based on DFT calculations, Pei and co‐workers theoretically compared the electronic structures of Au 10 (ECH 3 ) 10 , Au 12 (ECH 3 ) 9 , Au 20 (ECH 3 ) 16 , Au 23 (ECH 3 ) 16 , Au 24 (ECH 3 ) 18 , Au 25 (ECH 3 ) 18 , Au 28 (ECH 3 ) 20 , Au 36 (ECH 3 ) 24 , Au 38 (ECH 3 ) 24 , and Au 44 (ECH 3 ) 28 nanoclusters (E = S/Se) ( Figure ) . Calculated results demonstrated that the selenol‐protected Au nanoclusters with framework identical to the thiolated ones were stable local minima—all reaction energies (△ H ) for exchanging one S‐CH 3 ligand on thiolated nanoclusters into a Se‐CH 3 were negative (Figure ).…”
Section: Structures Of Ser‐stabilized Nanoclustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on DFT calculations, Pei and co‐workers theoretically compared the electronic structures of Au 10 (ECH 3 ) 10 , Au 12 (ECH 3 ) 9 , Au 20 (ECH 3 ) 16 , Au 23 (ECH 3 ) 16 , Au 24 (ECH 3 ) 18 , Au 25 (ECH 3 ) 18 , Au 28 (ECH 3 ) 20 , Au 36 (ECH 3 ) 24 , Au 38 (ECH 3 ) 24 , and Au 44 (ECH 3 ) 28 nanoclusters (E = S/Se) ( Figure ) . Calculated results demonstrated that the selenol‐protected Au nanoclusters with framework identical to the thiolated ones were stable local minima—all reaction energies (△ H ) for exchanging one S‐CH 3 ligand on thiolated nanoclusters into a Se‐CH 3 were negative (Figure ).…”
Section: Structures Of Ser‐stabilized Nanoclustersmentioning
confidence: 99%
“…Calculated results demonstrated that the selenol‐protected Au nanoclusters with framework identical to the thiolated ones were stable local minima—all reaction energies (△ H ) for exchanging one S‐CH 3 ligand on thiolated nanoclusters into a Se‐CH 3 were negative (Figure ). Accordingly, the reactions of Au m (SCH 3 ) n + n [HSeCH 3 ] → Au m (SeCH 3 ) n + n [HSCH 3 ] were all exothermic reactions, and thus such Au m (SeCH 3 ) n nanoclusters were more stable than their thiolated analogues …”
Section: Structures Of Ser‐stabilized Nanoclustersmentioning
confidence: 99%
“…Besides, the PBE functional with and without van der Waals correction were employed to calculate the relative energies of the isomer structures. 77,78 Both the PBE and PBE-D energies proposed that the thiolated Au 24 nanocluster favors configuration B when the substituent groups are CH 3 and CH 2 Ph-t Bu. Moreover, the predicted energy orders of configuration A and B for Au 24 (SCH 2 CH 2 Ph) 20 and Au 24 (SPh) 20 were found to be different, depending on the PBE or PBE-D functional used for calculations.…”
Section: Geometric Effects Of the Ligands Also Contribute To The Stabmentioning
confidence: 99%
“…However, it has been shown that a plasmon‐like response may be produced by AuNCs with as few as 23 Au atoms by changing the nature of the ligand . Further investigation is therefore required to establish the characteristics of this transition for different thiol and other functionalized ligands (e.g., selenoate groups), and it is through structural studies like these that our knowledge regarding the origin of the intrinsic size‐dependent properties of gold grows.…”
Section: Electronic Structure Calculationsmentioning
confidence: 99%
“…In addition to static structure determination, QM methods may also be used to investigate the dynamics of AuNP formation, including aspects such as self‐assembly/aggregation, doping, metal oxidation, ligand exchange,[16a,39,51] and the binding of small molecules to gold surfaces and nanoclusters …”
Section: Electronic Structure Calculationsmentioning
confidence: 99%